Forgery of Official Instruments - Bîrzu, Bogdan (Acta Universitatis Danubius. Juridica, 2022)
This study presents a brief analysis of the forgery of official instruments offence, through the lens of new regulations. The analysis included some resembling provisions, as well as differing provisions between the regulations in force and the previous one. Both the objective, as well as the subjective aspect of the offence have been taken into consideration, as well as some opinions about forms, modalities and legal precedents. Novelty elements concern both the analysis itself in relation to recent doctrine, as well as recent and relevant case law. The paper may be useful both for the academic environment, as well as for practitioners, and it will be published in the volume of a university course.